Strategi Pemanfaatan Media Sosial Facebook terhadap Peningkatan Penjualan Gula Aren - Yusril; Muh Tamrin; Inna Mutmainna Cahyani Thahir (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
This study aims to analyze the strategy of utilizing Facebook in palm sugar marketing, identify supporting and inhibiting factors, and evaluate its impact on increasing sales. This research method uses a descriptive qualitative approach, collecting data through observation, in-depth interviews, and documentation. Data analysis using the Miles and Huberman model, including data reduction, data presentation, and drawing conclusions, was conducted using the Nvivo12 application. The results indicate that Facebook has been utilized as a promotional and communication medium, but not optimally. Promotional activities are still limited to simple content with a low posting frequency. Of the three main indicators—content, interaction, and network—the informative and visual content aspects stand out, while interaction and network expansion still need improvement, as indicated by a slow response and limited use of group or marketplace features. The conclusion of this study confirms that the strategy of utilizing social media has the potential to increase palm sugar sales, but requires more optimal content planning, interaction management, and network utilization for maximum results. Keywords: Palm Sugar, Sales Increase, Social Media Utilization.